Analog Rice Production Training at the Sakinah Family Farmer Group (KWT) in Kulon Progo: Pelatihan Produksi Beras Analog Pada KWT Keluarga Sakinah Kulon Progo - Ichlasia Ainul Fitri; Chatarina Lilis Suryani; Bayu Kanetro; Dadang Mulyana; Ayu Pratiwi Nurhidayati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service activity was a collaboration between CSR Pertamina Parta Niaga Fuel Rewulu and Deparrtment of Food Technology, Faculty of Agroindustry, Universitas Mercu Buana Yogyakarta which conducted in the form of a training program on analog rice production for the Women Farmer Group (KWT) "Keluarga Sakinah" in Kulon Progo. The training was held over three days—on February 21, 24, and 28, 2025—at Dusun Pantog Kulon, Banjaroyo Village, Kalibawang District. The objective was to apply science and technology (IPTEKS) in the production of high-protein analog rice as a nutritious food alternative with added value and economic potential. The training included the preparation of "growol" flour from cassava and the production of analog rice enriched with cowpea flour. The outcome of this activity is expected to enhance the participants' skills, support local food security, and create entrepreneurial opportunities through functional food products.